2018
DOI: 10.1186/s13014-018-1137-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced parotid changes in oropharyngeal cancer patients: the role of early functional imaging and patient−/treatment-related factors

Abstract: BackgroundFunctional magnetic resonance imaging may provide several quantitative indices strictly related to distinctive tissue signatures with radiobiological relevance, such as tissue cellular density and vascular perfusion. The role of Intravoxel Incoherent Motion Diffusion Weighted Imaging (IVIM-DWI) and Dynamic Contrast-Enhanced (DCE) MRI in detecting/predicting radiation-induced volumetric changes of parotids both during and shortly after (chemo)radiotherapy of oropharyngeal squamous cell carcinoma (SCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…No study so far included the sublingual glands. All patients in these studies received primary or postoperative, curatively-intended, radio(chemo)therapy with IMRT [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [26], [27], [28] or 3D-radiotherapy [25], [27], [28]. Radiation doses to the primary tumor ranged from 60 to 74 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…No study so far included the sublingual glands. All patients in these studies received primary or postoperative, curatively-intended, radio(chemo)therapy with IMRT [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [26], [27], [28] or 3D-radiotherapy [25], [27], [28]. Radiation doses to the primary tumor ranged from 60 to 74 Gy.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that volumetric changes are also related to a greater or lesser degree of tissue vascularization. Patients with more vascularized parotid glands have a greater volume reduction, possibly due to increased tissue oxygenation, which leads to higher radiosensitivity of the gland [21]. Moreover, the reduced volume of parotid glands might be due to acinar loss or fibrosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of head‐and‐neck (HN) cancer, it has been shown that the combined use of D and D ∗ can increase the diagnostic accuracy in predicting malignancy in HN masses with respect to the ADC . In addition, IVIM can also be useful to assess the effect of radiotherapy in normal tissues, since they are usually irradiated during the treatment …”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, IVIM can also be useful to assess the effect of radiotherapy in normal tissues, since they are usually irradiated during the treatment. [9][10][11] The most reported approach for the estimation of D, D * and f in clinical research is a non-linear least square fitting of the IVIM signal on a voxel-wise basis, where the optimization algorithms classically employed are 13 and Trust Region 14,15 strategies. However, the goodness of fit of such a standard approach is strongly influenced by Signal-to-Noise Ratio (SNR) of the data, especially for the estimation of D * , making it difficult to assess small localized regions.…”
mentioning
confidence: 99%